2015
DOI: 10.1126/scisignal.2005596
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic activity of the kinase ZAP-70 mediates basal signaling and negative feedback of the T cell receptor pathway

Abstract: T cell activation must be properly regulated to ensure normal T cell development and effective immune responses to pathogens and transformed cells while avoiding autoimmunity. The mechanisms controlling the fine-tuning of T cell receptor (TCR) signaling and T cell activation are unclear. The Syk family kinase ζ chain–associated protein kinase of 70 kD (ZAP-70) is a critical component of the TCR signaling machinery that leads to T cell activation. To elucidate potential feedback targets that are dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 94 publications
(156 reference statements)
8
62
0
1
Order By: Relevance
“…We now report a critical role for a third site of tyrosine phosphorylation within the SH2 domain of Lck, Y192. Previously, we observed that this phosphosite was sensitive to Zap70 inhibition (Sjolin-Goodfellow et al, 2015). Because Zap70 is an Lck substrate, we speculated that phosphorylation of Y192 could participate in a negative feedback loop.…”
Section: Introductionmentioning
confidence: 85%
“…We now report a critical role for a third site of tyrosine phosphorylation within the SH2 domain of Lck, Y192. Previously, we observed that this phosphosite was sensitive to Zap70 inhibition (Sjolin-Goodfellow et al, 2015). Because Zap70 is an Lck substrate, we speculated that phosphorylation of Y192 could participate in a negative feedback loop.…”
Section: Introductionmentioning
confidence: 85%
“…Regardless of the differences likely resulting from stimulation with pervanadate or via the TCR and CD4, PAG showed low levels of tyrosine phosphorylation in both resting Jurkat cells and primary mouse CD4 + T cells. Moreover, following stimulation with both anti-TCR and anti-CD4 Abs and with pervanadate, PAG showed a dramatic increase in the level of tyrosine phosphorylation, which reached a maximum 2 min after stimulation (our study) (8,47). The consistent results obtained in these three independent phosphoproteomic studies are congruent with our biochemical analysis of the kinetics of PAG tyrosine phosphorylation following activation of CD4 + T cells with anti-TCR and anti-CD4 Abs, as well as with the kinetics of phosphorylation of PAG observed in many cell types in response to engagement of receptor tyrosine kinases, immunoreceptors, and integrins (15) However, they are difficult to reconcile with previous studies performed on mouse and human T cells that showed that PAG is constitutively phosphorylated in resting T cells and rapidly dephosphorylated once the TCR is engaged.…”
Section: Discussionmentioning
confidence: 97%
“…Those phosphorylated tyrosines include the binding site of CSK and FYN. Analysis of the phosphorylation kinetics of Y181, Y227, Y341, Y359, and Y417 in human PAG for up to 10 min after stimulating Jurkat T cells with anti-CD3 and anti-CD4 Abs showed that their phosphorylation steadily increased over the first 3 min of stimulation and then returned to ground state levels 10 min after stimulation (8,47). Therefore, the sustained tyrosine phosphorylation of PAG observed with pervanadate contrasts with the more transient tyrosine phosphorylation of PAG occurring in response to stimulation via the TCR and CD4, a difference that likely reflects the capacity of pervanadate to induce a potent and long-lasting inhibition of PTPases and that might alter the dynamics of the PAG interactome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from our lab have revealed previously uncharacterized negative feedback pathways from Vav1, Zap-70, SLP76, and PLCγ1 to receptor proximal signaling molecules in T cells [27, 42-46]. At this point, the vast majority of the phosphorylation sites on phosphopeptides with reduced abundance are not yet biologically characterized.…”
mentioning
confidence: 99%